A study of water environment purification efficiency by little duckweed Lemna minor L. from heavy metal salts using the energy of electromagnetic radiation and phytoremediant regeneration - O.A. Aref’eva; L.N. Ol’shanskaya; R.Sh. Valiev (Известия высших учебных заведений. Поволжский регион: Естественные науки, 2021)
Background. Works aimed at finding ecological and energy-saving technologies for water purification from heavy metals are very relevant. The purpose of this work is to study the methods of enhancing the completeness of copper, nickel and iron ions extraction from the aquatic environment of Lemna minor L. under the influence of EMP EHF, as well as its regeneration after the phytoremediation process in the presence of calcium cation additives in solutions. Materials and methods. A G4-142 high-frequency signal generator was used to study the processes of removing heavy metal ions (ITM) from model solutions using an electromagnetic field (EMP) with a frequency of 65 GHz. After EMP irradiation, Lemna minor L. plants were placed in model solutions based on settled tap water, simulating waste water containing heavy metal ions (ITM). The residual amount of ITM after phytoremediation was determined by voltammetric and photometric methods using a robotic complex “Expertise VA – 2D” with an electrode “3 in 1” and KFK-3. Histochemical methods were used in experiments on the regeneration of Lemna minor L. The statistical significance of the differences was carried out according to the medians in the samples, calculating the Kruskal – Wallis H-test. Results. As a result of the research, it was found that the efficiency of cleaning model solutions from copper ions by irradiated Lemna minor L. was 85–90 %. This indicator is slightly lower than the efficiency of cleaning the solution with Lemna minor L. not exposed to irradiation. The processes of copper extraction from solutions were influenced by the nature of the anion. Copper cations were better extracted from sulfate solution. The extraction of nickel ions by irradiated Lemna minor L. was more intense than by unirradiated Lemna minor L., but in both cases at low rates. The extraction efficiency of iron cations was 52–75 %. Experiments on regeneration of duckweed after phytoremediation showed that mother and daughter cells are more resistant to heavy metals than vegetative ones. Such resistance may be associated with the selectivity of the sensitivity of various plant organs to chemical agents. Conclusions. It was found that under the action of EHF EMR of the 65 GHz range, the process of extraction by duckweed cations of copper, iron and nickel proceeded more intensively. The efficiency of water purification from ITM reached 75–90 %. The influence of the radius of the cation and the size of the salt anion on the extraction rate of duckweed ITM was revealed. The positive effect of sulfate ions on the process of penetration of metals into the volume of duckweed phytomass is shown. The possibility of regeneration of duckweed after extraction of Ni2+ and Cu2+ ions (C = 1 and 10 mg/L) with or without the addition of calcium ions is shown. At the same time, duckweed fronds, after exposure to solutions with a copper cation content of 1 mg/l, with subsequent planting on a nutrient medium, retained the ability to produce buds and multiply. When the duckweed was kept in more concentrated media (Cu2+ 10 mg/l), even in the presence of calcium, the plants died, that is, no regeneration took place. With the content of nickel cation in the solution at concentrations of 1 and 10 mg/l, regeneration of duckweed was achieved in the presence of calcium ions. The regeneration of duckweed did not occur without calcium supplements.